2015
DOI: 10.3851/imp3017
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir/Emtricitabine Metabolites and Endogenous Nucleotide Exposures are associated with p16INK4a Expression in Subjects on Combination Therapy

Abstract: Background HIV may amplify immunologic, physiologic, and functional changes of aging. We determined associations of frailty phenotype, a T-cell senescence marker (p16INK4a expression), age, and demographics with exposures of the intracellular metabolites (IM) and endogenous nucleotides (EN) of tenofovir/emtricitabine (TFV/FTC), efavirenz (EFV), atazanavir (ATV), and ritonavir (RTV). Materials and Methods Plasma and PBMC samples for drug, IM, and EN concentrations were collected at 4 time points in HIV+ adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 17 publications
1
9
1
Order By: Relevance
“…This is consistent with a previous analysis of associations of exposures with age, frailty phenotype, and p16 INK4a expression 36. In a study evaluating trough concentrations measured during therapeutic drug monitoring, their analysis suggested no changes in EFV concentrations with age, with increased concentrations of protease inhibitors, such as ATV and RTV, although only 16.5% of these participants were 50 years old or older 37.…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with a previous analysis of associations of exposures with age, frailty phenotype, and p16 INK4a expression 36. In a study evaluating trough concentrations measured during therapeutic drug monitoring, their analysis suggested no changes in EFV concentrations with age, with increased concentrations of protease inhibitors, such as ATV and RTV, although only 16.5% of these participants were 50 years old or older 37.…”
Section: Discussionsupporting
confidence: 86%
“…The covariate relationship between TFV‐dp and FTC‐tp CL and p16 INK4a expression is novel, and is also associated with lower TFV‐dp and FTC‐tp exposures in these participants,27 as PBMC CL increases with higher expression of p16 INK4a . This observation is consistent with our hypothesis that increased cellular activation, which may be associated with senescence, increases the kinase activity responsible for the metabolism of the intracellular species.…”
Section: Discussionmentioning
confidence: 84%
“…Analytical methods have been previously described 27. All drug concentrations were determined in the UNC Center for AIDS Research Clinical Pharmacology and Analytical Chemistry Laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…TFV-dp, FTC-tp, dATP, and dCTP concentrations in peripheral blood mononuclear cells (PBMCs) were measured using LC-MS/MS in the UNC Center for AIDS Research Clinical Pharmacology and Analytical Chemistry Laboratory [12]. Drug exposure was measured as area under the curve (AUC) using non-compartmental analysis in Phoenix WinNonlin 6.3 (Pharsight, A Certara Company, St. Louis, MO); the linear up/log down trapezoidal method [22] was used to calculate AUC over the dosing interval.…”
Section: Methodsmentioning
confidence: 99%
“…In order to exert their antiviral effect, they must cross the cellular membrane and undergo phosphorylation to their respective metabolites, tenofovir diphosphate (TFV-dp) and emtricitabine triphosphate (FTC-tp). We previously demonstrated that higher expression of p16 INK4a is associated with lower exposures of FTC-tp, dATP, and dCTP in HIV-infected participants [12]. Inflammation may contribute to this relationship, as it has been shown to regulate drug transporters, such as breast cancer resistance protein (BCRP) and P-glycoprotein 1(P-gp), on cell membranes [13] capable of effluxing NRTIs and their metabolites [14, 15].…”
Section: Introductionmentioning
confidence: 99%